PENGARUH TERAPI DO’A TERHADAP KADAR LIMFOSIT PASIEN AIDS DI RUMAH SAKIT UMUM DAERAH DR. M. HAULUSSY AMBON - Wahyuni Aziza (Poltekkes Kemenkes Maluku, 2018)
National prevalence of AIDS in Inonesia at 2011 were 10,62/100.000 peoples, in Maluku until June2012 there was 782 HIV and 245 AIDS with 108 peoples mortality rate. Since 2012 has beendeveloped Comprehensive Continues Services in the public health services level. The services startedfrom preventif, early HIV’s test until treatment activities from various field including complementarymedicine thus increasing the quality of life of patients AIDS. The complementary therapy has been developed including spiritual therapy. Pray therapy is one of complementary therapy which can increase level of lymphocite. The aims of This research to determine effect of pray therapy tolymphocyte level. Methode of this study used quacy experiment with non randomized control groupdesign with pre test and post test. Samples in the study were 20 peoples. Data were analyzed by usingindependent T-Test with result showed pray therapy for 30 minutes twice day has a significant effect oflymphocyte level (CD4). This result an be used as a nursing therapy to give spirituality of patient.Nursing maneger can formulate a policy to provide nursing care holistically, provide a format forspiritual assessment and create programs to conduct spiritual nursing to clients. Keywords: HIV/AIDS, pray therapy, lymphocyte level (CD4)